Connectivity structures local population dynamics: a long‐term empirical test in a large metapopulation system. Issue 12 (1st December 2015) - Castorani, Max C. N.; Reed, Daniel C.; Alberto, Filipe; Bell, Tom W.; Simons, Rachel D.; Cavanaugh, Kyle C.; Siegel, David A.; Raimondi, Peter T.
Abstract : Ecological theory predicts that demographic connectivity structures the dynamics of local populations within metapopulation systems, but empirical support has been constrained by major limitations in data and methodology. We tested this prediction for giant kelp Macrocystis pyrifera, a key habitat‐forming species in temperate coastal ecosystems worldwide, in southern California, USA. We combined a long‐term (22 years), large‐scale ( 500 km coastline), high‐resolution census of abundance with novel patch delineation methods and an innovative connectivity measure incorporating oceanographic transport and source fecundity. Connectivity strongly predicted local dynamics (well‐connected patches had lower probabilities of extinction and higher probabilities of colonization, leading to greater likelihoods of occupancy) but this relationship was mediated by patch size. Moreover, the relationship between connectivity and local population dynamics varied over time, possibly due to temporal variation in oceanographic transport processes. Surprisingly, connectivity had a smaller influence on colonization relative to extinction, possibly because local ecological factors differ greatly between extinct and extant patches. Our results provide the first comprehensive evidence that southern California giant kelp populations function as a metapopulation system, challenging the view that populations of this important foundation species are governed exclusively by self‐replenishment.